The Teleost Thymus in Health and Disease: New Insights from Transcriptomic and Histopathological Analyses of Turbot, Scophthalmus maximus - Paolo Ronza; Diego Robledo; Ana Paula Losada; Roberto Bermúdez; Belén G. Pardo; Paulino Martínez; María Isabel Quiroga (Biology, 2020)
The thymus is a primary lymphoid organ that plays a pivotal role in the adaptive immune system. The immunobiology of the thymus in fish is considered to be similar to that of mammals, but it is actually poorly characterized in several cultured teleost species. In particular, while investigations in human and veterinary medicine have highlighted that the thymus can be affected by different pathological conditions, little is known about its response during disease in fish. To better understand the role of the thymus under physiological and pathological conditions, we conducted a study in turbot (Scophthalmus maximus), a commercially valuable flatfish species, combining transcriptomic and histopathological analyses. The myxozoan parasite Enteromyxum scophthalmi, which represents a major challenge to turbot production, was used as a model of infection. The thymus tissues of healthy fish showed overrepresented functions related to its immunological role in T-cell development and maturation. Large differences were observed between the transcriptomes of control and severely infected fish. Evidence of inflammatory response, apoptosis modulation, and declined thymic function associated with loss of cellularity was revealed by both genomic and morphopathological analyses. This study presents the first description of the turbot thymus transcriptome and provides novel insights into the role of this organ in teleosts’ immune responses.